Propuesta para el fortalecimiento del idioma inglés de los prestadores de servicios turísticos del sector hotelero del cantón Quevedo, provincia de Los Ríos, año 2022 - Zamora Gallardo, Jean Pierre (2022)
Ecotourism is a variant of tourism that involves many sectors and professional presence, for it is of vital importance that tourism professionals choose to have and acquire the best experience in all possible aspects. The purpose of this work of curriculum integration was to propose the strengthening of the English language of tourism service providers in the